2012
DOI: 10.1097/wno.0b013e31823c9b6c
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between NMO-Antibody and Anti–MOG Antibody in Optic Neuritis

Abstract: NMO-Ab and MOG-Ab could be potential biomarkers to determine visual prognosis in patients with ON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 24 publications
(22 reference statements)
1
41
1
Order By: Relevance
“…Furthermore, in our previous report, cases double positive for MOG-Abs and AQP4-Abs were particularly refractory to treatment, progressed rapidly, and tended to become resistant to treatment. 6 Case 4 in the present series was positive for both MOG-Abs and AQP4-Abs. In this case, despite courses of treatments, optic neuritis recurred repeatedly with residual visual field deficit resulting in no improvement in visual acuity.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Furthermore, in our previous report, cases double positive for MOG-Abs and AQP4-Abs were particularly refractory to treatment, progressed rapidly, and tended to become resistant to treatment. 6 Case 4 in the present series was positive for both MOG-Abs and AQP4-Abs. In this case, despite courses of treatments, optic neuritis recurred repeatedly with residual visual field deficit resulting in no improvement in visual acuity.…”
Section: Discussionmentioning
confidence: 78%
“…2,6,13,[16][17][18][19] Generally, measurement by enzyme-linked immunosorbent assay (ELISA) is influenced by the quantity and property of the protein, which may result in poor quantification and inadequate specificity. On the other hand, cellbased assay is performed by immunohistochemical staining and antigen-antibody reaction can be observed as fluorescence or coloration under a microscope, allowing confirmation of the presence of MOGAbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort, the 9 MOG antibody-positive patients did not have intrathecal oligoclonal bands or radiology consistent with MS, suggesting that this condition may be an immunologic entity that is distinct from both AQP4 antibody-positive NMO and MS. While we did not test a cohort of AQP4 antibodypositive patients for MOG antibodies in the context of this study, AQP4-and MOG-antibody double positivity has been seldom reported 23,24,39,40 ; therefore, the evaluation of the prevalence and clinical significance of double seropositive patients is a point of interest for future work.…”
mentioning
confidence: 99%
“…While observing thirty three eyes of 23 patients with optic neuritis and measuring their serum anti-MOG antibodies concentration, 34% of the cases were seropositive (and 26% of cases were seropositive for both MOG and NMO antibodies).This immunoglobulin is considered to be a biomarker to investigate visual prognosis in optic neuritis patients (30). A study on 37 cases, 18 or under 18 years old with recurrent or single episodes of optic neuritis, suggested that generally these patients had high titer serum anti-MOG antibodies from the subclass of IgG, especially in patients suffering from recurrent episodes of optic neuritis (31).…”
Section: Anti-mog Antibodies In Optic Neuritismentioning
confidence: 99%